SIGNIFICANCE OF RENAL FUNCTION IN TRAUMA: AN OBSERVATIONAL STUDY TO ASCERTAIN CORRELATION TO EGFR - Ahmed, Syed Faraz; Uzair, Muhammad; Saif, Anas Bin; Khan, Ahmed Mushtaq; Faraz, Saima (Pakistan Armed Forces Medical Journal, 2020)
Objective: To assess renal function in combat patients at the time of arrival from Balochistan in Accident & Emergency (A&E) of an ‘A’ Class Military Hospital.Study Design: Retrospective observational study with analysis to find correlation between measurable variables and glomerular filtration rate. Place and Duration Of Study:  Combined Military Hospital Malir Cantonment, Karachi, from October 2015 to October 2018.Material and Methods: All patients with major injuries (New Injury Severity Score NISS ≥16) were included in the study to assess kidney function by calculating their estimated glomerular filtration rate (eGFR) using serum creatinine. Correlation was calculated between eGFR and other variables which were pulse, mean arterial pressure, temperature and haemoglobin.Results: 75 patients were brought to A&E. 14 (18.66%) were brought in dead. There were 44 (58.6%) gunshot wounds, 14 (18.6%) blast injuries and 17 (22.6%) accidents post ambush attack. 26 (34.66%) were included in the study, with NISS ≥16. All patients were male with mean age 29.73 ± 5.08. 20 (77%) patients were fluid resuscitated in pre-hospital setting whereas 6 (23%) were not. Statistically significant correlations were found among eGFR and pulse rate, body temperature, mean arterial pressure, hemoglobin and NISS. 6 out of 26 patients not resuscitated in pre-hospital setting had a median eGFR of 53.5, as compared to median eGFR of 70 in 20 patients who were resuscitated before evacuation to CMH Malir, in the field medical units.Conclusion: Fluid resuscitation in the field lowers the possibility of renal dysfunction.